ASSESSMENT OF IMMUNIZATION SERVICE IN PERSPECTIVE OF BOTH THE RECIPIENTS AND THE PROVIDERS: A REFLECTION FROM FOCUS GROUP DISCUSSIONS - Mansuri, Farah Asad; Baig, Lubna A. (Journal of Ayub Medical College Abbottabad, 2003)
Objective: To assess the immunization services available through expanded program of immunizations (EPI) and national immunizations days (NIDs) and to determine the reasons for incomplete immunization. Background: A number of evaluations of the EPI program have been carried out either at a small scale or countrywide in order to identify statistical figures but very few of them reflect population opinions. Methods: This study is qualitative, based on eight focus Focus Group Discussions (FGDs) with mothers and fathers as recipients while lady health visitors and vaccinators as service providers. Results:Majority of the mother and fathers were aware of the importance of immunization. Overall the failure of immunization was related to low income, inaccessible government dispensaries and occupancy in house hold work. Almost all mothers and fathers were of the opinion that the private clinics are giving service at a higher cost for quality vaccines than that of government dispensaries. Majority of fathers and mothers are ignorant of the advantages of antenatal immunization. Vaccinators and Lady Health Visitors had adequate knowledge and were partly satisfied with the services they provide. Vaccinators identified the need of local vaccinators and well - run vehicles in order to increase immunization rate. Conclusion: The quality of immunization services is compromised at the recipient level mainly due to lack of motivation and prevailing doubts about immunization importance. The service providers thought that the problem of incomplete vaccination in rural or remote areas is because of improper vehicles, unavailability of local vaccinators particularly for females and misplacement of cards. Hence solving the problems of the providers at all levels combined with media campaigns to modify rigid behaviour of recipients can significantly improve the immunization coverage in Pakistan. Key words: vaccination, focus group, qualitative studies, mother’s and father’s perceptions, immunization